Entering the digital research age: Investigating the effectiveness of visual digital tools in agricultural research - Kawerau, Laura; Birkenberg, Athena; Daum, Thomas; Butele, Cosmas Alfred; Birner, Regina (SAGE Publications, 2024)
Agricultural studies mainly rely on quantitative research approaches. Despite growing interest in and uptake of qualitative, participatory, and visual methods due to their perceived advantages in gathering in-depth information and empowering participants, visual–digital research methods have yet to be largely applied. In our study on adaptation strategies to climate change among smallholder farmers in Uganda we compared different data collection methods, including: semi-structured interviews with manual note-taking, participatory impact diagrams, and adapted photovoice and cellphilm methodologies.